Analisis Strategi Pemasaran oleh Koperasi dalam Menarik Minat Beli Konsumen terhadap Produk Hasil UMKM - Reza Khairul Hadi; Retno Wulansari; Sunanto Sunanto (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
In the current era of competitive markets and growing student entrepreneurship, cooperatives (Koperasi) play an important role in supporting student innovation and promoting their products to a wider audience. However, the marketing strategies implemented by Koperasi Universitas Pamulang have not been fully evaluated in terms of their effectiveness in attracting consumer buying interest. This study aims to identify the extent of marketing strategies applied by the Koperasi and to analyze appropriate strategies to enhance consumer interest in products made by Universitas Pamulang students. This research employs a qualitative descriptive approach, which aims to describe and interpret real-life phenomena as they occur. The research method used is descriptive qualitative, with the object of research being the marketing strategies of Koperasi Universitas Pamulang. The subjects consist of 40 respondents, including 10 lecturers and 30 students who are members or consumers of the Koperasi. The data were collected through interviews, observations, recordings, and photographs, all reflecting actual field conditions. Data were analyzed using a qualitative descriptive analysis method, involving data reduction, data presentation, and conclusion drawing. The results show that improvements are needed in four dimensions: product quality, competitive pricing, store convenience, and promotion through affordable media such as banners and brochures to increase awareness and purchasing interest in student-made products.